Dear territory or dear partner? Causes and consequences of breeding dispersal in a highly territorial bird of prey with a strong pair bond - Passarotto Arianna; Morosinotto Chiara; Brommer Jon E; Aaltonen Esa; Ahola Kari; Karstinen Teuvo; Karell Patrik (SPRINGER, 2025)
Territorial species are unlikely to show extensive movements between breeding seasons. This is especially true for long-lived species, which often have strong pair bonding and can occupy the same territory for years. However, also in such species, individuals may face situations that can lead to a territory shift. Here, we use a comprehensive dataset documenting 40 years of breeding behavior in tawny owl (Strix aluco) - a long-lived species with high site tenacity and mate fidelity - to examine the factors affecting the decisions whether or not to move to another breeding territory and how far, as well as the fitness consequences thereof. We found that the likelihood and distance of movement in either sexes is strongly associated with a change of partner, indicating that mate loss may cause breeding dispersal. Moreover, mate change, not movement to a new territory, had negative effects on subsequent reproductive performance: individuals that changed partner were more likely to skip reproduction in the subsequent year and, in those cases they bred, they produced smaller clutches and raised fewer offspring. Our findings indicate that tawny owls change territory almost exclusively when searching for a new partner and that mate change has profound consequences on their subsequent breeding performance. Overall, our study provides evidence that in tawny owls territoriality and monogamy are associated and strongly linked to fitness, but mate fidelity may be more important than site fidelity, likely because sexes are involved in specific tasks and their cooperation ensures breeding success and, consequently, increases fitness.Significance statement Breeding dispersal, the movement of individuals between breeding sites, can entail high costs for animal fitness, especially for territorial species, which display strong site fidelity. We studied the factors associated with breeding dispersal and the consequences on breeding performances in tawny owl (Strix aluco), a highly territorial species. We found that tawny owls moved more frequently to another breeding territory when the mate died. Either sexes showed an equal probability to move, but the effect was stronger in females than in males after a mate change. Moreover, owls that changed partner showed delayed reproduction, smaller clutch and a higher probability to skip reproduction. Our findings show that in tawny owls territoriality and monogamy are associated and strongly linked to fitness, but mate fidelity may be more important than site fidelity, likely because sexes share the costs of holding the territory.